Designing & teaching learning goals & objectives - Marzano, Robert J. (Bloomington, IN : Marzano Research Laboratory, 2009)
This resource demonstrates how to design and teach effective learning goals and objectives by following strategies based on the strongest research and theories available. This book includes a short summary of the key research behind these classroom practices and shows how to implement them using step-by-step, hands-on strategies. Short quizzes help readers assess their understanding of the instructional best practices explained in each section.
Research and theory -- Developing specific learning goals and tasks -- Developing learning goals at different levels of difficulty in the service of differentiation -- Organizing learning goals into a scale -- Teaching in a system of learning goals.
Includes bibliographical references (p. 127-131) and index.
Keywords: Learning strategies; Effective teaching; Education -- Aims and objectives